2022
DOI: 10.3389/fnagi.2022.788846
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Markers for Cognitive Impairment in Parkinson’s Disease: Current View

Abstract: Cognitive impairment (CI) ranging from mild cognitive impairment (MCI) to dementia is a common and disturbing complication in patients with Parkinson’s disease (PD). Numerous studies have focused on neuropathological mechanisms underlying CI in PD, along with the identification of specific biomarkers for CI. Magnetic resonance imaging (MRI), a promising method, has been adopted to examine the changes in the brain and identify the candidate biomarkers associated with CI. In this review, we have summarized the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Rs-fMRI can detect leukoaraiosis and a wide range of brain dysfunction (Cheng et al, 2017 ). In addition, other MRI techniques such as small vessel disease-related MRI, neuromelanin-sensitive MRI, diffusion-weighted imaging, cerebrovascular abnormality-related MRI, resting fMRI, and proton magnetic resonance spectroscopy can provide imaging features that can predict the degree of cognitive impairment in AD (Hou and Shang, 2022 ). Early studies have shown that mild cognitive impairment is a precursor to early clinical signs of AD, and changes in WM volume during this period may be of great value in clinical practice (Pergher et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rs-fMRI can detect leukoaraiosis and a wide range of brain dysfunction (Cheng et al, 2017 ). In addition, other MRI techniques such as small vessel disease-related MRI, neuromelanin-sensitive MRI, diffusion-weighted imaging, cerebrovascular abnormality-related MRI, resting fMRI, and proton magnetic resonance spectroscopy can provide imaging features that can predict the degree of cognitive impairment in AD (Hou and Shang, 2022 ). Early studies have shown that mild cognitive impairment is a precursor to early clinical signs of AD, and changes in WM volume during this period may be of great value in clinical practice (Pergher et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rs-fMRI can detect leukoaraiosis and a wide range of brain dysfunction (Cheng et al, 2017). In addition, other MRI techniques such as small vessel diseaserelated MRI, neuromelanin-sensitive MRI, diffusion-weighted imaging, cerebrovascular abnormality-related MRI, resting fMRI, and proton magnetic resonance spectroscopy can provide imaging features that can predict the degree of cognitive impairment in AD (Hou and Shang, 2022). Early studies have shown that mild cognitive impairment is a precursor to early clinical signs of AD, and changes in WM volume during this period may be of great value in clinical practice (Pergher et al, 2020).…”
Section: Hotspots and Research Status On Mri Of Wm In Admentioning
confidence: 99%
“…Rs-fMRI can detect leukoaraiosis and a wide range of brain dysfunction (Cheng et al, 2017). In addition, other MRI techniques such as small vessel diseaserelated MRI, neuromelanin-sensitive MRI, diffusion-weighted imaging, cerebrovascular abnormality-related MRI, resting fMRI, and proton magnetic resonance spectroscopy can provide imaging features that can predict the degree of cognitive impairment in AD (Hou and Shang, 2022). Early studies have shown that mild cognitive impairment is a precursor to early clinical signs of AD, and changes in WM volume during this period may be of great value in clinical practice (Pergher et al, 2020).…”
Section: Hotspots and Research Status On Mri Of Wm In Admentioning
confidence: 99%